2017
DOI: 10.3389/fmicb.2017.00929
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptome Analysis Reveals Extensive Alternative Splicing Events in the Protoscoleces of Echinococcus granulosus and Echinococcus multilocularis

Abstract: Alternative splicing (AS), as one of the most important topics in the post-genomic era, has been extensively studied in numerous organisms. However, little is known about the prevalence and characteristics of AS in Echinococcus species, which can cause significant health problems to humans and domestic animals. Based on high-throughput RNA-sequencing data, we performed a genome-wide survey of AS in two major pathogens of echinococcosis-Echinococcus granulosus and Echinococcus multilocularis. Our study revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…Moreover, the biological activity of sorafenib tosylate may be due, in addition, to its actions against other targets (e.g., VEGFR, PDGFR, and Flt3) in this situation. However, according to recent studies, there are no known orthologs of VEGFR, PDGFR, or Flt3 expressed in Echinococcus spp., although the literature mentions the presence of a VEGF signaling pathway in E. multilocularis and E. granulosus (7,46). Therefore, at present, the parasiticidal effect of sorafenib tosylate could be only partially attributed to its inhibition of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the biological activity of sorafenib tosylate may be due, in addition, to its actions against other targets (e.g., VEGFR, PDGFR, and Flt3) in this situation. However, according to recent studies, there are no known orthologs of VEGFR, PDGFR, or Flt3 expressed in Echinococcus spp., although the literature mentions the presence of a VEGF signaling pathway in E. multilocularis and E. granulosus (7,46). Therefore, at present, the parasiticidal effect of sorafenib tosylate could be only partially attributed to its inhibition of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 98%
“…On the one hand, considering that the synthesized cDNA represents the set of transcribed genes, it is possible that these receptors are not being transcribed in the larval stage of protoscoleces. On the other hand, it has been reported that in this larval stage, 33% of the genes are subject to alternative splicing, so it is also feasible that the genes corresponding to Eg2DBDβ and Eg2DBDγ undergo a process of this type in which case the primer hybridisation regions could be absent [43]. In this case, only Eg2DBDα isoform is expressed in protoscoleces.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it plays an important role in characterizing gene expression and regulation [11]. Whole-genome sequencing, proteomic analyses, and transcrip-tomic investigations have been used to identify the differentially expressed genes (DEGs) and proteins in the different life stages (adult, oncosphere, hydatid cyst, larval worms, and pepsin/H+-activated PSCs) of E. granulosus [12][13][14][15]. However, the transcriptomic features of PSCs in the encystation process have not yet been described.…”
Section: Introductionmentioning
confidence: 99%